Structural Characteristics of the Lens in Presenile Cataract - Andjelic, Sofija; Drašlar, Kazimir; Hvala, Anastazija; Hawlina, Marko (Frontiers in Medicine, 2021)
The purpose of this work is to examine the structure of the lens epithelial cells (LECs) of presenile idiopathic cortical cataract in order to investigate possible structural reasons for its development. The anterior lens capsules (aLC: basement membrane and associated lens epithelial cells) were obtained from routine uneventful cataract surgery of 5 presenile cataract patients (16 and 41 years old females and 29, 39 and 45 years old males). None of the patients had family history of cataract, medication or trauma and they were otherwise healthy. None had any other abnormal features in the ocular status except cataract. The aLCs were prepared for scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The most prominent abnormal features observed by SEM for all 5 studied presenile cataract patients were the changes of the LECs structure with the dents on the apical side centrally toward the nucleus. TEM also showed the thinning of the lens epithelium with the segmentally concave cells and the compressed and elongated nuclei. Abnormal, distinguishable structural features were observed in the anterior lens epithelium LECs in all 5 presenile cataract patients. Disturbed structure of LECs, specific for presenile cataract type is shown that may play a role in water accumulation in the presenile idiopathic cortical cataract lens.